Pharmacokinetic modeling and simulation support for age‐ and weight‐adjusted dosing of dabigatran etexilate in children with venous thromboembolism. (26th March 2021) - Röshammar, Daniel; Huang, Fenglei; Albisetti, Manuela; Bomgaars, Lisa; Chalmers, Elizabeth; Luciani, Matteo; Halton, Jacqueline; Mitchell, Lesley G.; Bergstrand, Martin; Ibrahim, Moustafa M. A.; Joseph, David; Tartakovsky, Igor; et al.
Abstract: Background: Dabigatran etexilate (DE), a direct oral thrombin inhibitor, has been evaluated in children with venous thromboembolism (VTE) using oral solution, pellets, or capsules. Objectives: This study evaluated DE pharmacokinetics (PK) in children with VTE and the appropriateness of a DE pediatric age‐ and weight‐based dosing algorithm. Patients/Methods: A population PK model was fitted to data from four single‐arm and one randomized, comparative pediatric VTE studies (358 children aged birth to <18 years; 2748 PK observations) and one healthy‐adult study (32 males aged <40 years; 1523 PK observations) using nonlinear mixed‐effects modeling. A stepwise, covariate, model‐building procedure evaluated the influence of covariates (e.g., age, body weight, body surface area [BSA]‐normalized renal function, and sex). The final model was used to evaluate the pediatric dosing algorithm, with simulations comparing pediatric trough exposure with reference exposure defined for the pediatric studies. Results: The population PK of dabigatran was adequately described by a two‐compartment model with first‐order elimination and absorption. Age, weight, BSA‐normalized renal function, and sex were statistically significant covariates (all P < .05). Apparent clearance increased with age (independently of body weight), diminished with decreasing BSA‐normalized renal function, and was lower in females than males. All disposition parameters increased with body weight escalation (allometric scaling). Simulations confirmed that for all DE formulations, the final pediatric dosing algorithms achieved reference exposure without dose adjustment. Conclusions: Using a population PK model of DE for children with VTE, simulations showed that the final dosing algorithms were appropriate for all DE formulations; no dose titration was needed.